Estudio de líquido sinovial en equinos fina sangre de carrera con fractura de carpo tipo esquirla - Godoy P., Adolfo; Pinto P., Enrique; Acuña B., Mario; Garcés, Hernán (Monografías de Medicina Veterinaria, 1993)
This study was realized in 55 thoroughbred horses in training. The horses ranged in age from 2 to 4 years, with a chip fracture at the carpus. The fractures where in different stages of evolution. The fractured horses where compared with horses who had no history of fractures, in the same range of age and in training. In all horses an arthrocentesis of the carpus was realized, obtaining of each one 5 ml of sinovial liquid. The sinovial liquid was analized for total proteins, aldehid groups and mucine clot. A significant increase of (p < 0.05) proteins and sinovial aldehid groups was observed in all sick horses. Sinovial aldehid werw increased in the older fractures